2004
DOI: 10.1007/bf02708481
|View full text |Cite
|
Sign up to set email alerts
|

X-ray structure determination and analysis of hydrogen interactions in 3, 3′-dimethoxybiphenyl

Abstract: The crystal structure of 3,3′ ′-dimethoxybiphenyl has been determined by X-ray diffraction methods with an aim of describing the hydrogen interaction in biphenyl derivatives. The title compound crystallizes in monoclinic space group P2 1 /c with unit cell dimensions, a = 7⋅ ⋅706(1), b = 11⋅ ⋅745(2), c = 12⋅ ⋅721(2) Å, β β = 92⋅ ⋅31(1)°, Z = 4 and its structure has been refined up to the reliability index of 3⋅ ⋅8%. The average torsion angle about the interring CC bond is 37⋅ ⋅5°. The O1 and O1′ ′ atoms of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…This structural parameter is particularly important because it affects each dye molecule’s degree of π conjugation, which will affect its photophysical properties. For the DPA-Ph n -CAA family of molecules (Table S1 in the Supporting Information), we found that their π-spacers ( n > 1) are nonplanar between the two neighboring Ph rings with dihedral angles in the range 30–35° (the average value is 34.1°), which is close to the inter-ring dihedral angle of 37.5° in the crystal structure of 3,3′-dimethoxybiphenyl determined by X-ray diffraction methods . These results indicate the steric repulsion between two neighboring Ph rings.…”
Section: Resultssupporting
confidence: 70%
“…This structural parameter is particularly important because it affects each dye molecule’s degree of π conjugation, which will affect its photophysical properties. For the DPA-Ph n -CAA family of molecules (Table S1 in the Supporting Information), we found that their π-spacers ( n > 1) are nonplanar between the two neighboring Ph rings with dihedral angles in the range 30–35° (the average value is 34.1°), which is close to the inter-ring dihedral angle of 37.5° in the crystal structure of 3,3′-dimethoxybiphenyl determined by X-ray diffraction methods . These results indicate the steric repulsion between two neighboring Ph rings.…”
Section: Resultssupporting
confidence: 70%